2011
DOI: 10.1111/j.1468-4446.2010.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Social disparities in children's vocabulary in early childhood. Does pre‐school education help to close the gap?1

Abstract: Children start school with differing levels of skills. Thus, children of different social origin have different probabilities of educational success right from the start of their school career. This paper analyses how the gap in language abilities of children with different social backgrounds develops from age three to five. A focus lies on the question whether pre-school education can help to close this gap. The data of the UK Millennium Cohort Study (MCS) show that children's score on a standardized vocabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 37 publications
4
50
1
9
Order By: Relevance
“…From the perspective of the smart city, a favorable family learning environment not only become the basis of making progress in the workplace for parents, but also as the driving force of expanding educational activities into museums for children. The past studies about the family learning environment almost all concerned about the impact on children, especially on children's growth (Anders et al, 2012;Becker, 2011;Foster et al, 2005). However, in this study, the results showed that the family learning environment also have a certain influence on parents' career development.…”
Section: Discussioncontrasting
confidence: 54%
“…From the perspective of the smart city, a favorable family learning environment not only become the basis of making progress in the workplace for parents, but also as the driving force of expanding educational activities into museums for children. The past studies about the family learning environment almost all concerned about the impact on children, especially on children's growth (Anders et al, 2012;Becker, 2011;Foster et al, 2005). However, in this study, the results showed that the family learning environment also have a certain influence on parents' career development.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, children from higher socioeconomic backgrounds had a higher level of vocabulary than those from lower socioeconomic backgrounds (Hoff, 2003). Similarly, children's scores on the vocabulary task of the British Ability Scales battery depended heavily on parental education (Becker, 2011). Thus, children whose parent(s) had a high educational level had a broader vocabulary than children whose parents had a lower educational level.…”
Section: Discussionmentioning
confidence: 98%
“…It seems that the way parent(s) interact with their children and the stimulation they offer (e.g. reading books) is helpful for language development as well as the socioeconomic level (Becker, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…O ile jednak uczęszczanie do przedszkoli często nie doprowadza do zrównania wyników dzieci, to bez uczęszczania do nich różnice pomiędzy wynikami edukacyjnymi byłyby jeszcze większe (Becker, 2011).…”
Section: Równość Szansunclassified